Socio-economic factors affecting the organizational commitment of academic librarians in Manila area - Mojica, Michael Anthony A. (2008)
The purpose of this study is to determine the level of organizational commitment of the professional librarians working in private institutions in the Manila area. It seeks to determine if the socio-demographic factors like age, gender, civil status, monthly income, educational attainment and length of employment have significant effects in the organizational commitment of these librarians.